Transient Ionospheric Upflow Driven by Poleward Moving Auroral forms Observed During the Rocket Experiment for Neutral Upwelling 2 (RENU2) Campaign. Issue 12 (28th June 2019) - Burleigh, M.; Zettergren, M.; Lynch, K.; Lessard, M.; Moen, J.; Clausen, L.; Kenward, D.; Hysell, D.; Liemohn, M.
Abstract: This study examines cumulative effects of a series of poleward moving auroral forms on ion upflow and downflow. These effects are investigated using an ionospheric model with inputs derived from the Rocket Experiment for Neutral Upwelling 2 (RENU2) sounding rocket campaign. Auroral precipitation inputs are constrained by all‐sky imager brightness values resulting in significant latitudinal structuring in simulated ionospheric upflows due to transient forcing. For contrast, a case with steady forcing generates almost double the O + upflow transport through 1, 000 km when compared to poleward moving auroral form‐like structures. At high altitudes, model results show a spread in upflow response time dependent on ion mass, with molecular ions responding slower than atomic ions by several minutes. While the modeled auroral precipitation is not strong enough to accelerate ions to escape velocities, source populations available for higher‐altitude energization processes are greatly impacted by variable forcing exhibited by the RENU2 event. Key Points: Imager data provide realistic transient forcing constraints for model inputs to simulate observations from a high‐latitude rocket flight Transient forcing deposits energy over a wider latitudinal region but less energy in any specific location Modeling a sequence of poleward moving auroral forms with realistic spatiotemporal variability generates significant latitudinal structuring